AUDIT SYSTEM FOR USAGE OF BLOOD PRODUCT IN SANGLAH GENERAL HOSPITAL DENPASAR BALI - Kadek Mulyantari; Teguh Triyono; Usi Sukorini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Blood transfusion is one of very important therapy components. One indicator of the blood services quality in Sanglah General Hospital Denpasar Bali Indonesia is achieving the target of unused blood order ≤ 10% per month. However, these targets have not been achieved. The number of unused blood orders reached 6,719 bags per year (600 bags per month or 21.5%). Unused blood orders is mostly from Department of Internal Medicine (40.9%), followed by Department of Surgical (35.6%), Department of Obstetrics and Gynecology (15.5%) , and Department of Pediatrics (8%). The high number of unused blood orders can causes several problems such as the disorder of blood supply, inefficiency of pre-transfusion testing and decreased quality of blood product. Considering the consequences of high unused blood order, it is necessary to conduct a research on audit system for usage of blood product in Sanglah Hospital.The aim of study are to analyze the influence of audit system to reduce unused blood order and to decrease the number of C/T ratio. The study design was a pre and post test intervention study. The population in this study were all forming of blood requests in Sanglah Hospital. The sample is blood request form Department of Internal Medicine of the last two months. Intervention in this study was the development and dissemination of guidelines for usage of blood products, followed by concurrent audit and prospective audit of the sample.The study show there are decline of unused blood orders and C/T ratio before and after implementation of the audit system for usage of blood products. Reduction of unused blood order in Sanglah Hospital is 5.4%, and in the Department of Internal Medicine is 5.2%. The causes of unused blood orders were patient died, overestimation of blood order, transfusion delays because waiting for the schedule of hemodialysis, the patient has a fever, blood product has expired, and the occurrence of administration errors. Reduction of C/T ratio in Sanglah Hospital is 0,094 and in the Department of Internal Medicine is 0,072. Audit system for usage of blood products can reduce unused blood orders and decrease C/T ratio.